AN ANALYSIS OF PARENT-TEACHER COMMUNICATION TOWARD THE STUDENTS’ READING COMPREHENSION - Burhan Burhan; Agung Rinaldy Malik; Diyenti Rusdin; Marzuki Marzuki (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2021)
ABSTRACT The aims of this research are to find out that extent parents are involved in their children reading comprehension at home and to know the factors trigger the communication between parents and the English teacher toward the students reading comprehension. By using the qualitative research this study described the research finding using a triangulation technique to gather the data from the questionnaires, interview, and Focus Group Discussion (FGD) from 10 parents and one english teacher at SMA Negeri 1 Lampasio. The data analysis indicates two things. The first, parents role toward the students’ reading comprehension is Low. It was found by the result of questionnaire that showed there were 10%-20% parents involved in their child reading comprehension at home. The second, the factors triggers the communication between parents and the English teacher were progress report that given by the English teacher to parents used an examination sheet and the same living place between parents and the English teacher. Keywords: Parent-Teacher Communication, Reading Comprehension